Periodic use of time-varying state feedbacks for the receding horizon control of bilinear systems - Lee, Y; Kouvaritakis, B; Cannon, M (2008)
This paper provides a receding horizon control method for bilinear systems in the presence of input constraints. Periodically-invariant sets are derived for a bilinear system with respect to a series of time-varying state feedback gains. The dual-mode control strategy is adopted and the periodically-invariant sets are used as target invariant sets. The state feedback gains used to define the target invariant sets are also used to render degrees of freedom to steer the current state into the target set. The region of attraction for the proposed algorithm is enlarged significantly with an extension of the horizon of periodicity while the on-line computation remains easy to handle. Copyright © 2007 International Federation of Automatic Control All Rights Reserved.